A new measure of equity duration: The duration-based explanation of the value premium revisited - David Schröder; Florian Esterer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper uses analysts' forecasts to estimate a share's equity duration, a measure of a company's average cash-flow maturity. We find that short duration equity is associated with high expected and realized returns, which cannot be attributed to the shares' systematic risk exposure as implied by the market beta. Instead, we show that equity duration is a priced risk factor with similar properties as the Fama-French value factor B/M ratio. Our analysis suggests that the value premium might be a compensation for the value firms' higher exposure to cash-flow risk.
Keywords: G12; M41; G15; 330